PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENJUAL BAHAN BAKAR MINYAK ECERAN DI KOTA PEKANBARU - Reski Aslamiah Lubis; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Law Number 22 Year 2001 concerning Oil and Gas regulates upstream business and downstreambusiness in the commercial sector and can be implemented after obtaining permission from the government.This study raises the issue of retailers of fuel oil who do not have permission from the government but do notimplement criminal law enforcement processes. The purpose of this research is also to first discuss how lawenforcement against retail oil fuel sellers is linked to Law Number 22 Year 2001 concerning Oil and Gas.The second is what is the reason for the seller of oil-based fuels to do fuel oil trading without permissionfrom the government. Researchers use research methods with juridical sociological approaches.This research method uses primary data, namely data obtained directly from the field, and alsosecondary data, namely literature studies using primary legal materials secondary legal materials, andtertiary legal materials. The data is then used to describe an object problem in the form of synchronizing thefacts that occur with the applicable laws and regulations.Based on the results of the study, it can be seen that the criminal act of selling retail fuel has notbeen running as it should because of a lack of socialization between the government and the publicregarding the procedures for trading fuel oil, then a lack of legal awareness in this case the retailercomplies with criminal provisions 22 of 2001 concerning oil and gas, increasing economic needs is thereason people sell fuel in retail and the length of the process of making business licenses is the reason forconducting ecran fuel trading without permission.Keywords : Law Enforcement, Retail Fuel Seller, Justice